WASH YOUR HANDS AFTER WAKE UP (Study of Ma'anil Hadith): WASH YOUR HANDS AFTER WAKE UP (Study of Ma'anil Hadith) - Deo Saputra; Muhajirin, Muhajirin; Almunadi, Almunadi (CV. Doki Course and Training, 2023)
ABSTRACT This study describes the existence of waking up from sleep taught by Rosulullah to wash hands first, this is done to avoid impurity and prudence in worship. The problem in this study is: How to understand the hadith of washing hands when waking up? This study generally aims to find out the understanding of the hadith of washing hands when waking up. The theory used in completing this research is ma'anil hadith. This research is literature research, which is all research based on searching for data in the literature, a type of qualitative research. This research is based on data collected from literature and then analyzed. The data analysis technique used in this study is qualitative descriptive, which is a data analysis that includes a general, systematic, and comprehensive description. So that the data is analyzed and a conclusion is drawn. This study resulted in findings that the understanding of hadith washes hands after waking up, to practice the sunnah of the Prophet and be careful in worship. Because when sleeping, of course, there is no known presence of feces on one's hands, the Prophet SAW recommended washing hands 3 times even though the feces are not necessarily there.